HUMAN RIGHTS DEFENDERS AND NEW VOICES IN THE PURSUIT OF SOCIAL JUSTICE - Costa, Claudia Márcia; dos Santos, Marco Aurelio Moura (ARACÊ, 2025)
This paper discusses the crucial role of human rights defenders and the emergence of new voices in contemporary activism. In the current context, there is a growing participation of marginalized and vulnerable groups in the defense of their rights, driving significant social change. However, these defenders face numerous acts of violence and threats that undermine their efforts and put their lives at risk. The struggle for human rights has been characterized by persistent challenges. Advocates engaged in social and political causes frequently encounter physical violence, death threats, intimidation, and criminalization. These attacks are intended to silence their voices and deter the defense of fundamental rights. Despite these obstacles, many defenders remain resilient and committed to their cause, confronting adversity and continuing the fight for social justice. A notable shift in the activist landscape is the emergence of adolescents and young people who have become prominent figures in human rights advocacy. Greta Thunberg and Malala Yousafzai are two inspiring examples of young activists who have achieved global impact. Through their courageous actions, they have brought urgent issues—such as the climate crisis and girls’ education—to the forefront of international discourse. The participation of young activists underscores the importance of amplifying the voices of future generations and recognizing their potential in building a more just world. These voices have influenced policy and mobilized communities worldwide, emphasizing the need for an inclusive and intergenerational approach to the promotion of human rights. In this context, it is essential to support and protect human rights defenders, particularly those facing heightened risks. Strengthening national and international legal frameworks to ensure the safety and freedom of these defenders, while creating safe spaces for their voices to be heard and valued, is imperative. In conclusion, the activism of human rights defenders plays a vital role in the pursuit of social justice, despite the constant acts of violence and threats that hinder their efforts. The rise of young and marginalized voices—such as Greta Thunberg (20), Malala Yousafzai (25), Amanda Gorman (25), Catarina Silva (20), Isaias Hernandez (25), Txai Suruí (26), and Manu Gaspar (25)—highlights the importance of expanding representation and inclusion in human rights discussions. Supporting and protecting these defenders is fundamental to ensuring a more just and equitable future for all.